Service Quality Dimension and Customers' Satisfaction: An Empirical Study of Tesco Hypermarket in Malaysia - Padmalini Singh; Ranjith PV; Nuramalin Fathihah; Daisy Mui Hung Kee; Nuralina Nuralina; Nurdiyanah Nurdiyanah; Nursyahirah Nursyahirah (AIBPM Publisher, 2021)
With the rapid growth of the hypermarket industry in Malaysia, it is hard to investigate customers' preferences towards a particular hypermarket. Increasing competition is shrinking the customer base further. Tesco Hypermarket has been one of the leading hypermarkets in Malaysia for years. This study investigates the customers' satisfaction towards the service quality dimension of the Tesco Hypermarket in Malaysia. In this study, the service quality of tangibles, reliability, responsiveness, assurance, and empathy are employed. The process of evaluating service quality was performed quantitatively, with a total of 300 customers participating in our questionnaire. A SERVQUAL questionnaire has been structured to measure the impact of service quality dimensions on customer satisfaction. The study’s findings suggest that all the gap scores are negative, explaining that the expectation of customer satisfaction regarding the hypermarket is higher than their perception.